2023
DOI: 10.3390/v15030687
|View full text |Cite
|
Sign up to set email alerts
|

Intranasal Boosting with Spike Fc-RBD of Wild-Type SARS-CoV-2 Induces Neutralizing Antibodies against Omicron Subvariants and Reduces Viral Load in the Nasal Turbinate of Mice

Abstract: The emergence of new immune-evasive severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) variants and subvariants outpaces the development of vaccines specific against the dominant circulating strains. In terms of the only accepted immune correlate of protection, the inactivated whole-virion vaccine using wild-type SARS-CoV-2 spike induces a much lower serum neutralizing antibody titre against the Omicron subvariants. Since the inactivated vaccine given intramuscularly is one of the most commonly used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…Our previous studies have shown that subcutaneous or intramuscular immunization with HR121 protein in Freund's or aluminum adjuvant induces strong neutralizing antibodies that provide effective protection against SARS-CoV-2 infection in hACE2 mice, Syrian golden hamsters and rhesus macaques 13 . Recently, a large number of studies have demonstrated that intranasal delivery of SARS-CoV-2 vaccines with some appropriate adjuvants or viral vectors can promote mucosal immune responses 33 . Due to the immunogenicity of HR121, it may induce mucosal antibodies that neutralize its antiviral activity after multiple intranasal administration.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous studies have shown that subcutaneous or intramuscular immunization with HR121 protein in Freund's or aluminum adjuvant induces strong neutralizing antibodies that provide effective protection against SARS-CoV-2 infection in hACE2 mice, Syrian golden hamsters and rhesus macaques 13 . Recently, a large number of studies have demonstrated that intranasal delivery of SARS-CoV-2 vaccines with some appropriate adjuvants or viral vectors can promote mucosal immune responses 33 . Due to the immunogenicity of HR121, it may induce mucosal antibodies that neutralize its antiviral activity after multiple intranasal administration.…”
Section: Discussionmentioning
confidence: 99%
“…Active recombinant human ACE2 (Gln18‐Ser740) expressed in HEK293 cells was sourced commercially (ABclonal; Cat#: RP01277). In addition, we expressed human ACE2 (Ser19‐Arg708) in‐house using a baculovirus insect cell system as described previously 18 . Both commercial and in‐house ACE2 peptides were characterized using sodium dodecyl sulfate‐polyacrylamide gel electrophoresis (SDS‐PAGE) and western blot analysis using a monoclonal antibody against ACE2 (R&D Systems; Cat#:AF933).…”
Section: Methodsmentioning
confidence: 99%
“…In addition, we expressed human ACE2 (Ser19-Arg708) in-house using a baculovirus insect cell system as described previously. 18 Both commercial and in-house ACE2 peptides were characterized using sodium dodecyl sulfatepolyacrylamide gel electrophoresis (SDS-PAGE) and western blot analysis using a monoclonal antibody against ACE2 (R&D Systems; Cat#:-AF933). Detailed protocols for in-house ACE2 expression and western blot analysis are described in the Supporting Information Material.…”
Section: Ace2 Peptidesmentioning
confidence: 99%
“…Intranasal vaccines offer the valuable benefit of inducing robust tissue-resident memory B and T cell responses within the respiratory system, thereby providing swift and potent primary defense against mucosal pathogens [ 102 , 103 ]. Cai et al [ 104 ] conducted a study that demonstrated the effectiveness of one or two intranasal boosts of the fragment crystallizable (Fc)-linked RBD-binding domain derived from the wild-type SARS-CoV-2 (Wuhan-Hu-1) in inducing significantly higher neutralizing antibodies against Omicron subvariants, including BA.5.2 and XBB.1. The combination of intramuscular priming and intranasal boosting can provide broader cross-protection against Omicron variants and subvariants, with the potential to prolong the interval needed for updating the vaccine immunogen from months to years [ 104 , 105 ].…”
Section: Main Textmentioning
confidence: 99%